Carbon Fiber Composites of Pure Polypropylene and Maleated Polypropylene Blends Obtained from Injection and Compression Moulding - D. Pérez-Rocha; A. B. Morales-Cepeda; F. Navarro-Pardo; T. Lozano-Ramírez; P. G. LaFleur (International Journal of Polymer Science)
A comparative study of the mechanical performance of PP and PP/PP-g-MAH blends reinforced with carbon fibre (CF) obtained by two different moulding techniques is presented. Three filler contents were used for fabricating the composites: 1, 3, and 5 pph (parts per hundred). The crystallisation behaviour of the composites was studied by differential scanning calorimetry. Morphological and structural features of these samples were observed by atomic field microscopy and Fourier-transform infrared spectroscopy, respectively. Mechanical properties of the injection and compression moulded composites were evaluated by means of tensile and impact resistance tests. The fracture surface of the impacted samples was observed by scanning electron microscopy. The processing method had a noticeable effect on the results obtained in these tests. Young’s modulus was enhanced up to 147% when adding 5 pph CF to a PP matrix when processed by compression moulding. Addition of PP-g-MAH and CF had a favourable effect on the tensile and impact strength properties in most samples; these composites showed improved performance as the filler content was increased.